The Role Of Mediation Of Buying Interest In Halal Certification And Price Perception On Purchase Decisions In Restaurants In Medan City - Arif, Muhammad; Wulandari, Dea Ayu (CERED Indonesia Institute, 2024)
This study aims to determine the Effect of Halal Certification and Price Perception on Purchasing Decisions Through Purchase Intention as an Intervening Variable at Nyushiin Medan Restaurant. The method used in this study is a quantitative method with a population of all consumers of Nyushiin Medan Restaurant. The data collection technique used Accidental Sampling with 100 samples. The data analysis technique for this study used statistical analysis, namely partial least square - structural equation model (SEM - PLS). This study successfully found that Halal Certification has no significant effect on Purchasing Decisions. Price Perception has a significant effect on Purchasing Decisions. Purchase Intention has a significant effect on Purchasing Decisions. Halal Certification does not have a significant effect on Purchase Intention. Price Perception has a significant effect on Purchase Intention. Halal Certification through Purchase Intention on Purchasing Decisions has no positive effect. Price Perception through Purchase Intention on Purchasing Decisions is significant